Proposed Design of Assistant Tools to Reduce the Risk of Disorders (MSDS) Operator of Weaving Work Station CV XYZ - Panji Yudha Pratama; Nora Azmi; Indah Permata Sari (OPSI, 2022)
The weaving operator of CV XYZ has an unergonomic work posture with a bent back and unbalanced legs at work. This non-ergonomic condition was identified by using the Nordic Body Map questionnaire to find out complaints on 28 body parts of three operators. From the identification of weaving operators using a nordic body map, it is known that there are complaints on the back, waist, and hips of the body. Identification using the Rapid Entire Body Assessment method shows that the final result of the assessment is 11, which means that there is a need for improvement now on the operator's work posture. The results of the QEC method show an exposure score of 97.12% for operator 3 and the action that must be taken is research and changes now. To reduce the risk of high work posture, a proposal for improving the working posture of the weaving machine set up operator was formulated by designing a manual scissor lift tool. In the process of designing tools, Indonesian anthropometric data is needed. The stages of designing tools are identifying operator needs, conceptualizing tools using a need metric matrix, selecting tools concepts with combination tables and scoring concepts and describing the design of tools using AutoCAD and CATIA software. From the results of the selection of several alternative concepts, a tool in the form of a manual scissor lift was chosen which has a combination of elements, namely a square working platform design, using 2 hydraulics and raw materials made of steel. Meanwhile, the manual scissor lift specification has a maximum height of 85 cm, a footing length of 70 cm and a footing width of 46 cm. It is known that before the proposed improvement, the final result of the REBA score was 11 and after the improvement the final result of the REBA score was 4 which indicates that the operator's work posture has improved after using the assistive device, especially in the arms, legs and back of the operator